The HIV Pre-exposure Prophylaxis (PrEP) Cascade at NYC Sexual Health Clinics: Navigation Is the Key to Uptake. (1st April 2020) - Pathela, Preeti; Jamison, Kelly; Blank, Susan; Daskalakis, Demetre; Hedberg, Trevor; Borges, Christine
Abstract : Background: Clinics providing sexual health care pose unique opportunities to implement HIV pre-exposure prophylaxis (PrEP) programs. The PrEP program at New York City's Sexual Health Clinics provides intensive on-site navigation for linkage to PrEP care. We assessed uptake of this intervention. Methods: We categorized men who have sex with men (MSM) without HIV hierarchically as having had (1) HIV post-exposure prophylaxis (PEP) use (past year); or (2) selected sexually transmitted infections (STI) (past year); or (3) HIV-diagnosed sex/needle-sharing partners (past 6 months); or (4) expressed interest in PrEP (day of clinic visit). We constructed PrEP cascades and used multivariable regression to examine acceptance of PrEP navigation, referral to a PrEP provider, linkage (<60 days), and PrEP prescription. Results: One thousand three hundred one of 2106 PrEP (62%) patients accepted navigation. Of those, 55% (718/1301) were black or Hispanic MSM. STI and PEP patients had lowest navigation acceptance levels (35%–46%). Of navigated patients, 56% (628/1114) accepted referrals, 46% (288/628) linked to PrEP providers, and 82% (235/288) were prescribed PrEP; overall, 11% of those offered navigation (235/2106) received prescriptions. Navigated MSM with PEP history [adjusted prevalence ratio (aPR) 1.34, 95% confidence interval (CI): 1.16 to 1.56)], previous STI (aPR 1.28, 95% CI: 1.12 to 1.45), or HIV-diagnosed partners (aPR 1.18, 95% CI: 1.01 to 1.37) were more likely than those with PrEP interest to accept referrals. Probability of linkage varied by insurance status; prescription did not vary by patient factors. Conclusions: Although MSM in key priority groups (eg, previous STI) showed low navigation uptake, those who accepted navigation were likely to be referred for PrEP, suggesting a need for expanded up-front engagement.